(Un)employment and skillsformation in Chile: An explorationof the effects of training in labourmarket transitions - Juan A. Bogliaccini; Aldo Madariaga; Miski Rojas Peralta; Soledad Marzoa (International Labour Organization (ILO), 2022)
Labour markets are currently undergoing tremendous challenges. Automation, skilled-biased technological change, or offshoring are transforming challenges and opportunities for workers. In this context, international organizations have highlighted the crucial role of labour market policies and institutions, particularly but not exclusively re-training and skills formation policies, to cope with the said transformations and allow individuals to better adapt and benefit from them (for example, ILO 2017; OECD 2019). Existing research on the effects of labour market changes and skills formation has concentrated on advanced economies. There is limited knowledge about the impact of skills formation and training in Latin America (ILO 2016), in part due to a lack of information and data on training programmes, particularly longitudinal data. In this paper, we analyse the effects of training on labour market transitions in Chile, using available longitudinal data. We focus on the transitions from unemployment to employment and between different types of employment. Using individual-level panel data spanning seven years of individuals' work trajectories and training instances, we estimate the average effect of attending training courses while unemployed on individuals' yearly ratio of unemployment. In addition to this, we explore whether training improves the probability of workers changing occupational categories. Our results suggest that there is a small but still significantly positive effect of training in reducing post-training unemployment events. For employed workers, results show how training occurs mostly among highly educated workers or workers in very specific occupations, which limits the potential equalizing effects of training policies.
Keywords: 330; decent work; future of work; employment; unemployment; quality of working life; productive development; productivity